Gender differences in quality of life and the course of schizophrenia: national study. Issue 2 (1st March 2022) - Rotstein, Anat; Shadmi, Efrat; Roe, David; Gelkopf, Marc; Levine, Stephen Z.
Abstract : Background: Evidence from various sources suggests that females with schizophrenia tend to report lower quality of life than males with schizophrenia despite having a less severe course of the disorder. However, studies have not examined this directly. Aims: To examine gender differences in the association between quality of life and the risk of subsequent psychiatric hospital admissions in a national sample with schizophrenia. Method: The sample consisted of 989 (60.90%) males and 635 (39.10%) females with an ICD-10 diagnosis of schizophrenia. Quality of life was assessed and scored using the Manchester Short Assessment of Quality of Life. The course of schizophrenia was assessed from the number of psychiatric hospital admissions. Participants completed the quality of life assessment and were then followed up for 18-months for subsequent psychiatric admissions. Hazard ratios (HR) from Cox proportional hazards regression models were estimated unadjusted and adjusted for covariates (age at schizophrenia onset and birth year). Analyses were computed for males and females separately, as well as for the entire cohort. Results: A subsample of 93 males and 55 females was admitted to a psychiatric hospital during follow-up. Higher quality of life scores were significantly ( P < 0.05) associated with a reduced risk of subsequent admissions among males (unadjusted: HR = 0.96, 95% CI 0.93–0.99; adjusted HR = 0.96, 95% CI 0.93–0.99) but not among females (unadjusted: HR = 0.97, 95% CI 0.93–1.02; adjusted HR = 0.97, 95% CI 0.93–1.02). Conclusions: Quality of life in schizophrenia is a gender-specific construct and should be considered as such in clinical practice and future research.